NO LIQUID IMMISCIBILITY IN THE SYSTEM MGSIO3-SIO2 AT 5.0 GPA - Dalton J.A.; Presnall D.C. (My University, 1997)
Liquidus phase relationships in the system MgSiO3-SiO2 at 5.0 GPa have been determined using a multianvil apparatus. Compared to phase relationships at 1 atm, the MgSiO3-SiO2 phase diagram at 5.0 GPa is significantly different in two respects. First, the composition of the eutectic between MgSiO3 and SiO2 moves from 65.0 wt% SiO2 at 1 atm/1547°C (protoenstatite-cristobalite eutectic; Bowen and Andersen, 1914) to 68.8 wt% SiO2 (orthoenstatite-coesite eutectic) at 5.0 GPa/1930°C. Second, no stable two-liquid field is present in the MgSiO3-SiO2 system at 5.0 GPa. The unbroken coesite liquids curve is inflected indicating the presence of a submerged, metastable miscibility gap below the liquidus. Thus, although the temperature of the solvus critical point is likely to increase with pressure, the dT/dP slope of the SiO2 liquidus is much steeper and as a result, the immiscibility dome has become submerged completely. The reduction in liquid immiscibility in the MgSiO3-SiO2 system at 5.0 GPa implies that in more complex systems relevant to the Earth, immiscibility will also be suppressed at high pressures.